2008
DOI: 10.1002/nbm.1230
|View full text |Cite
|
Sign up to set email alerts
|

MRI in ocular drug delivery

Abstract: Conventional pharmacokinetic methods for studying ocular drug delivery are invasive and cannot be conveniently applied to humans. The advancement of MRI technology has provided new opportunities in ocular drug-delivery research. MRI provides a means to non-invasively and continuously monitor ocular drug-delivery systems with a contrast agent or compound labeled with a contrast agent. It is a useful technique in pharmacokinetic studies, evaluation of drug-delivery methods, and drug-delivery device testing. Alth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 101 publications
0
20
0
1
Order By: Relevance
“…For MRI, anesthesia was used only for gel instillation and after 2 h to do the MRI. Due to the large amount of water retained by the polymer into the gel, the incorporation of MRI probes was not necessary because water increased the signal intensity in MRI T2 allowing the visualization of the gel [34]. MRI studies were conducted in a horizontal 9.4 T magnetic resonance (Bruker BioSpin, Ettlingen, Germany) 20 cm diameter hole with gradients of 440 mT/m.…”
Section: In Vivo Evaluation Of Time Permanence Of Gel In the Eye Surfacementioning
confidence: 99%
“…For MRI, anesthesia was used only for gel instillation and after 2 h to do the MRI. Due to the large amount of water retained by the polymer into the gel, the incorporation of MRI probes was not necessary because water increased the signal intensity in MRI T2 allowing the visualization of the gel [34]. MRI studies were conducted in a horizontal 9.4 T magnetic resonance (Bruker BioSpin, Ettlingen, Germany) 20 cm diameter hole with gradients of 440 mT/m.…”
Section: In Vivo Evaluation Of Time Permanence Of Gel In the Eye Surfacementioning
confidence: 99%
“…Ocular pharmacokinetic studies have provided useful information on the distribution of drugs in the eye and in the development of novel drug delivery methods. In addition to conventional pharmacokinetic approaches of tissue dissection, methods such as microdialysis (13), fluorophotometry (14), and magnetic resonance imaging (MRI) (15) have been used in the studies of ocular pharmacokinetics and to determine the routes of drug delivery and clearance after periocular, intrascleral, and intravitreal administration. Despite these recent efforts in studying the mechanisms and pharmacokinetics of ocular drug delivery, the distribution and clearance after ocular drug delivery are still difficult to predict (16).…”
Section: Introductionmentioning
confidence: 99%
“…The investigation of ocular pharmacokinetics by traditional methods is invasive and can severely disturb the biodistribution of pharmaceuticals during dissection in animals (10). Recent studies have demonstrated the feasibility of MRI for noninvasive monitoring of the biodistribution of pharmaceuticals in the body in drug delivery research (9,1113).…”
Section: Introductionmentioning
confidence: 99%